Grammatical relations and grammatical categories in Malay; The Indonesian prefix "meN-" revisited - Tjia, Johnny (Wacana, Journal of the Humanities of Indonesia, 2015)
The lexical roots of Malay are flexible with regard to their grammatical categories, which presents a problem in providing grammatical evidence for their category determination. This paper attempts to propose the use of affixes as one way to deal with the issue. Data from Indonesian and Ambon (Malay) language are among others given for clarification. The grammatical evidence from Indonesian active meN-, together with other affixes, are revisited as they can contribute to our understanding of the matter.